2015
DOI: 10.18632/oncotarget.5674
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagy promotes metastasis and glycolysis by inducing ROS in gastric cancer cells

Abstract: Autophagy defect has been shown to be correlated with malignant phenotype and poor prognosis of human cancers, however, the detailed mechanisms remain obscure. In this study, we investigated the biological changes induced by autophagy inhibition in gastric cancer. We showed that inhibition of autophagy in gastric cancer cells promotes epithelial-mesenchymal transition (EMT) and metastasis, alters metabolic phenotype from mitochondrial oxidative phosphorylation to aerobic glycolysis and converts cell phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 50 publications
(60 reference statements)
2
76
0
1
Order By: Relevance
“…Furthermore, it has been demonstrated that acetylation of Beclin-1 can lead to inhibition of autophagic responses [23]. Indeed, knockdown of Beclin-1 in GC cells results in inhibition of autophagy, which in turn promotes EMT and metastasis [29]. Immunohistochemistry is another indispensable tool for the evaluation of autophagy in situ [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that acetylation of Beclin-1 can lead to inhibition of autophagic responses [23]. Indeed, knockdown of Beclin-1 in GC cells results in inhibition of autophagy, which in turn promotes EMT and metastasis [29]. Immunohistochemistry is another indispensable tool for the evaluation of autophagy in situ [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, at cellular level these barriers represent numerous interfaces of tissues and organs with ambient and internal environment to sustain structural, immune and metabolic integrity. From this perspective, while macroautophagy, microphagy and chaperone-mediated autophagy execute barrier functions at molecular and membrane levels [2,5,6,[13][14][15][16][17], it would be reasonable to assume that dynamics and efficacy of autophagy function can determine performance of the barrierforming cells. Note, in the vertebrates the infection cellular barriers are constituted by multidimensional interactive networks of mesenchymal, epithelial, reticuloendothelial, endothelial and hematopoietic cells, where along with monocytes and polymorphonuclear granulocytes, a particular role in xenobiotic control and "cleaning function" is attributed to nonprofessional phagocytes, e.g., skin fibroblasts, bone marrow stromal cells, endothelial and epithelial cells [18,19].…”
Section: Autophagy and Intrinsic Biological Barriersmentioning
confidence: 99%
“…That infers increasing burden of autophagy function in nonprofessional phagocytes when professional phagocytes are depleted due to pathological conditions. Furthermore, considering that nonprofessional phagocytes can also orchestrate response to acute stress or trauma by expression and massive release of paracrine and endocrine factors, such as damage-associated molecular patterns (DAMPs), inflammatory cytokines, proteases, chemokines, defensins, nitric oxide, ROS, fragmented DNA, exosomes and microvesicles, which in turn can trigger and propagate autophagy stress response [6,[14][15][16][17][18][19].…”
Section: Autophagy and Intrinsic Biological Barriersmentioning
confidence: 99%
See 2 more Smart Citations